CAPTURING RANDOM-EFFECT META-ANALYSIS TOWARD SCIENTIFIC INQUIRY LEARNING APPROACH IN SCIENCE EDUCATION - Kusuma, Mobinta; Wilujeng, Insih; Susongko , Purwo; Retnawati, Heri; Santoso, Purwoko Haryadi; Yuenyong, Chokchai; Ariyatun, Ariyatun (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Implementing scientific inquiry as a learning approach has accounted for most discussion topics and research areas in science education. Numerous studies have been conducted for decades; therefore, synthesizing the updated results will be worthwhile. Diverse needs require effective implementation of the vision of scientific inquiry for scientists, and various forms of learning output pose a challenge for scholars to provide a systematic summary of evidence regarding its role in science teaching and learning. Therefore, the random effect model was suitable for this paper to capture the impact of scientific inquiry on science learning comprehensively. A meta-analysis study using a random-effects model was chosen to systematically synthesize 22 academic articles gathered from the Scopus and Web of Science indexing databases. An individual paper was first extracted for its sample size, mean, and corresponding standard deviation, which were then calculated to measure the effect size of each piece of evidence using the JASP program. In summary, we highlight the positive and moderate impact of scientific investigation on student learning outcomes as a promising approach to enhancing science learning. This study fills the gap in the previous literature by providing a cross-cultural systematic synthesis of Indonesian and non-Indonesian literature, as well as comprehensively measuring the effects of scientific inquiry interventions. These findings support scientific inquiry as a promising approach to learning and encourage the sustainability of efforts to enhance the quality of science learning in various educational contexts.